Development of TPACK for teacher-educators: A technological pedagogical content knowledge scale - Beri, Nimisha; Sharma, Lalit (Linguistics and Culture Review, 2021)
The purpose of this study is to develop a valid and reliable TPACK (technological pedagogical content knowledge) scale based on the core components of TPACK framework in order to measure teacher-educators’ TPACK. For this purpose, 46 statements were developed and tested by 5-point Likert type scale. Data were collected from 642 teacher educators working in different colleges of education under different universities in state of Punjab. The collected data was analyzed by using SPSS 22.0 software. The Exploratory Factor Analysis (EFA) was carried out in order to investigate the factor structure of the scale. EFA resulted in six factors named as Pedagogical skills, Creative thinking skills, Ethics, Instructional design, Innovativeness and Virtual learning environment. The Cronbach’s Alpha coefficient for the whole scale was calculated as .848. The KMO value was calculated as .889 and the Bartlett’s Test of Sphericity examined (chi-square = 17196.73; df = 1035), which is significant (P-Value<.001). Based on result and in comparison with the Cronbach’s alpha coefficient values for other TPACK surveys in the literature as a whole and for their sub-components the TPACK scale established here can be said to have a high level of reliability in terms of its factors and as a whole.